Pathological Fracture: An Unusual Presentation in Childhood Chronic Myeloid Leukemia - Mururul Aisyi; Ayu Hutami Syarif; Anita Meisita; Agus Kosasih; Achmad Basuki; Resti Mulya Sari (Indonesian Journal of Cancer, 2019)
Introduction: Chronic Myeloid Leukemia is a hematological malignancy driving from myeloproliferative process. It is typified by the presence of the Philadelphia chromosome manifesting in certain distinct complications, including pathological fracture. Pathological fracture is recognized as an extramedullary disease that occurs as a result of transformation of CML into blast crisis phase.Case Presentation: Here, we report a case of pediatric male CML. After being failed with imatinib therapy, he turned to nilotinib and was unable to achieve a major molecular response. He presented with high blast count and pain in the left arm. He was diagnosed with pathological fracture and blast crisis phase CML. Taken the young age and displacement of fracture into consideration, he was conservatively treated by a combination of immobilization and a higher dose of targeted therapy, nilotinib. The 2-month evaluation revealed clinical union and reduction of blast cells.Conclusions: Regarding the minimal displacement and age presentation, pathological fracture in pediatric CML requires non-invasive treatment and optimization of antileukemic therapy.